## câu1 a 5. (x-7) = 7. (x-3) b3. (x-8)-6.(x-5)=12 c7.(x-4)-3.(x+8)=-84 d 6. (x-3)=8.(x-4) e 19-|2x+3|=-6 câu 2 3x+4y-xy=15

Question

câu1
a 5. (x-7) = 7. (x-3)
b3. (x-8)-6.(x-5)=12
c7.(x-4)-3.(x+8)=-84
d 6. (x-3)=8.(x-4)
e 19-|2x+3|=-6
câu 2
3x+4y-xy=15

in progress 0
2 tháng 2021-10-24T23:45:33+00:00 2 Answers 5 views 0

1. $a, 5.(x-7)=7.(x-3)$

$⇔5x-35=7x-21$

$⇔5x-7x=-21+35$

$⇔-2x=14$

$⇔x=-7$

$b,3.(x-8)-6.(x-5)=12$

$⇔3x-24-6x+30=12$

$⇔-3x=12+24-30$

$⇔-3x=6$

$⇔x=-2$

$c,7.(x-4)-3.(x+8)=-84$

$⇔7x-28-3x-24=-84$

$⇔4x=-32$

$⇔x=-8$

$d,6.(x-3)=8.(x-4)$

$⇔6x-18=8x-32$

$⇔-2x=-14$

$⇔x=7$

$e,19-|2x+3|=-6$

$⇔19-2x-3=-6$

$⇔-2x=-22$

$⇔x=11$

2. \text{~~Holi~~}

1.

a. 5(x-7)=7(x-3)

-> 5x-35=7x-21

-> 5x-7x=-21+35

-> -2x=14

-> x=(14)/(-2)

-> x=-7

Vậy x=-7

b. 3(x-8)-6(x-5)=12

-> 3x-24-6x+30=12

-> 3x-6x=12+24-30

-> -3x=6

-> x=6/(-3)

-> x=-2

Vậy x=-2

c. 7(x-4)-3(x+8)=-84

-> 7x-28-3x-24=-84

-> 7x-3x=-84+28+24

-> 4x=-32

-> x=(-32)/4

-> x=-8

Vậy x=-8

d. 6(x-3)=8(x-4)

-> 6x-18=8x-32

-> 6x-8x=-32+18

-> -2x=-14

-> 2x=14

-> x=7

e. 19-|2x+3|=-6

-> |2x+3|=19-(-6)

-> |2x+3|=25

-> 2x+3=±25

->$$\left[ \begin{array}{l}2x+3=25\\2x+3=-25\end{array} \right.$$

->$$\left[ \begin{array}{l}x=11\\x=-14\end{array} \right.$$

Vậy x\in{11;-14}